Pyrrolidinium‐PEG Ionic Copolyester: Li‐Ion Accelerator in Polymer Network Solid‐State Electrolytes. Issue 44 (13th October 2021) - Choi, Young Gyun; Shin, Jong Chan; Park, Anseong; Jeon, Young Min; Kim, Jin Il; Kim, Sebin; Kim, Seulwoo; Lee, Won Bo; Lee, Minjae; Park, Jong Hyeok
Abstract: Nonflammable lithium‐ion batteries (LIBs) are developed by adapting polymer solid electrolytes, but their insufficient electrochemical performance has not been fully addressed to date. Crosslinked polymer gel electrolytes with minimal organic solvents (hard gels) are proven to be nonflammable electrolytes, but their lithium metal battery performance is not comparable to those of conventional liquid electrolyte‐based systems. Here, a semi‐interpenetrating polymer network (semi‐IPN) ion‐transporting solid film that comprises a UV‐curable crosslinked polymer and tailored linear pyrrolidinium‐polyethylene glycol copolyester ion channels (named PN PEG), is reported. PN PEG can solvate Li + effectively with the help of carbonate solvents. Molecular dynamics (MD) simulations confirm that Li + transportation is accelerated due to the weaker interaction between PN PEG and Li + ions than between the solvents and ions. The semi‐IPN electrolyte with PN PEG exhibits a flexible, nonflammable nature with an ionic conductivity of 4.2 × 10 −1 mS cm −1 and Li + transference number of 0.51. The individual pyrrolidinium‐Bis(trifluoromethanesulfonyl)imide (pyrrolidinium‐Tf2 N) monomer and PEG chain ratios in PN PEG strongly affect battery performance, and the optimized semi‐IPN‐based lithium metal half cells with LiCoO2 cathodes show greatly improved discharge capacity retention at high c‐rate conditions owing to effective Li + transportation and excellent cycling performance (93.8% capacity retention after 200 cycles at 0.5 C). Abstract : Tailored linear pyrrolidinium‐polyethylene glycol (pyrrolidinium‐PEG) copolyester with solvated lithium hexafluorophosphate in carbonate organics is dispersed in a UV‐crosslinkable polymer matrix to fabricate a solid‐state semi‐interpenetrating network polymer electrolyte system. Well‐dispersed pyrrolidinium‐PEG copolyester can accelerate Li + transportation between the cathode and anode and exhibits a flexible, nonflammable nature with an ionic conductivity of 4.2 × 10 −1 mS cm −1 .